2006
DOI: 10.1109/tevc.2005.851275
|View full text |Cite
|
Sign up to set email alerts
|

A faster algorithm for calculating hypervolume

Abstract: Abstract-We present an algorithm for calculating hypervolume exactly, the Hypervolume by Slicing Objectives (HSO) algorithm, that is faster than any that has previously been published. HSO processes objectives instead of points, an idea that has been considered before but that has never been properly evaluated in the literature. We show that both previously studied exact hypervolume algorithms are exponential in at least the number of objectives and that although HSO is also exponential in the number of object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
303
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(303 citation statements)
references
References 22 publications
0
303
0
Order By: Relevance
“…The major drawback of the hypervolume indicator is its high computation effort; all known algorithms have a worst-case runtime complexity that is exponential in the number of objectives, more specifically O.N n 1 / where N is the number of solutions considered (Knowles 2002;While et al 2006). A different approach was presented by Fleischer (2003) who mistakenly claimed a polynomial worst-case runtime complexity - While (2005) showed that it is exponential in n as well.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The major drawback of the hypervolume indicator is its high computation effort; all known algorithms have a worst-case runtime complexity that is exponential in the number of objectives, more specifically O.N n 1 / where N is the number of solutions considered (Knowles 2002;While et al 2006). A different approach was presented by Fleischer (2003) who mistakenly claimed a polynomial worst-case runtime complexity - While (2005) showed that it is exponential in n as well.…”
Section: Related Workmentioning
confidence: 99%
“…The fitness values I k h .a; A; R/ can be calculated on the fly for all individuals a 2 A by a slightly extended version of the "hypervolume by slicing objectives" (Zitzler 2001;Knowles 2002;While et al 2006) algorithm, which traverse recursively one objective after another. It differs from existing methods in that it allows (1) to consider a set R of reference points and (5) to compute all fitness values, e.g., the I 1 h .a; P; R/ values for k D 1, in parallel for any number of objectives instead of subsequently as in Beume et al (2007).…”
Section: Extended Scheme For Environmental Selectionmentioning
confidence: 99%
“…HV is a performance indicator to measure the quality of solution sets obtained by MOEAs in terms of both convergence and diversity [61]. The method for calculating HV value is the same to that adopted in [23].…”
Section: Approximate Non-dominated Sorting For Many-objective Optimizmentioning
confidence: 99%
“…A lot of research has focused on improving the computational complexity of this indicator [29,30,31,32]. The exact computation of the algorithm has been shown to be #P-hard [33] in the number of objectives.…”
Section: Multi-objective Art-based Edamentioning
confidence: 99%